Problems of Precambrian paleomagnetism on the territory of Ukraine - V. Bakhmutov; I. Polyachenko; S. Cherkes (Геофизический журнал, 2018)
Some problems of paleomagnetic research of the Precambrian rocks of Ukraine are considered. The results of paleomagnetic researches of the Proterozoic rocks of the Ukrainian Shield, Ediacaran traps of Volyn and sedimentary rocks of Podolia were analyzed. With the emergence of many new isotopic age data for the Ukrainian Shield rocks we have new opportunities to get reliable palaeomagnetic poles. But our studies of the pilot collections of samples from some key outcrops in the Middle Dnieper, Azov, Dniester-Bug, Ingul and North-Western crustal blocks of the Ukrainian Shield with modern geochronological isotopic ages showed their absence of informativity for palaeo-magnetic determinations. On the Ukrainian Shield the gabbro-anorthosite and granite rapakivi of Korosten and Korsun-Novomyrhorod anorthosite-mangerite-charnockite-granite complexes in the northwestern and central part of the shield are good candidates for palaeomagnetic investigations. New paleomagnetic pole (Φ = 22.7°N, Λ = 164.3°E, dp/dm = 4.9°/9.6°) for ages of 1750 Ma were calculated for six sites within Ingul mega-block. Based on the analysis of paleomagnetic poles for Fennoscandia and the Ukrainian Shield the model of relative position and orientation of these blocks at 1770 and 1750 Ma were calculated. About 1770 Ma Fennoscandia and the Ukrainian Shield occupied low latitudinal positions (15° N and 2° S respectively). At the same time the Ukrainian Shield was rotated anticlockwise about 40° relatively to Fennoscandia. In the next 20 Ma Fennoscandia and the Ukrainian shield drifted southward at about 5° and occupied 10°N and 7°S paleolatitudes respectively, but relative rotation of blocks almost did not occur. The average speed of latitudinal drift of both blocks was near to 2.8 cm/yr. The new results of paleomagnetic studies of Volhyn basalts of Ratnenska suite are presented. We assume that the geometry of the geomagnetic field was not dipole as one of the interpretation of these results. In this context we should study of whole Volyn traps sequence from boreholes and Ediacaran—Cambrian sequences of Podolia in order to gather some data about frequency of geomagnetic reversals.